Trade Competitiveness of the Middle East and North Africa : Policies for Export Diversification - Lopez-Calix, Jose R. (World Bank, 2012)
International trade was deeply affected by the global financial and economic crisis. Mimicking worldwide trends, imports from and exports to the Middle East and North Africa dropped significantly in 2009. This sudden decline in global trade should not divert attention away from four major developments in global economic integration that have shaped the region's trade policies and performance over the past decade: the emergence of global supply chains, the growth of trade in services, the rise of China and India as major international trading powers, and regional integration. The first development is the rise of global production networks in which different stages of the production of a single good occur at different locations. As a result of this development, consumer products often contain parts, components, and inputs from a large number of countries. The second major trend relates to trade in services. With the wave of liberalization and of information and communications-related technological developments, off-shoring in services such as back-office work processes, call center operations, medical transcription, accounting, and legal research has boomed. India is a good example of a country that has hugely benefited from this trend. The third important development is the emergence of China and India as new trade, innovation, and growth poles alongside the United States and Europe. The fourth development is the increase in regional and preferential trade agreements, which have been proliferating, not least because progress in multilateral trade negotiations under the auspices of the World Trade Organization has been slow. Integration with selected partners can help countries reap benefits from international integration while avoiding the large-scale adjustment needs that are often associated with broader-based trade reforms. The Middle East and North Africa comprises countries that are resource-poor but labor-abundant, resource-rich and labor-abundant, and resource-rich and labor-importing, each displaying its own idiosyncrasies. The eleven chapters of this volume examine the region's trade policy reforms and performance by focusing on the four key developments in international trade, with a twist. Instead of examining production chains as such, the volume focuses on export diversification (part one), a major development challenge in the region, especially for oil exporters. It then explores services trade (part two), the relations with China and India (part three), and regional integration (part four).